Low-Cost Methods for Molecular Characterization of Mutant Plants : Tissue Desiccation, DNA Extraction and Mutation Discovery: Protocols /: Tissue Desiccation, DNA Extraction and Mutation Discovery: Protocols. (2015) - Till, Bradley J; Jankowicz-Cieslak, Joanna; Huynh, Owen A; Beshir, Mayada M; Laport, Robert G; Hofinger, Bernhard J
No abstract available